Versatile Intercom System / Norsuzila Nadzri and Noor Fadzlina Mustafa - Nadzri, Norsuzila; Mustafa, Noor Fadzlina (2005)
The Versatile Intercom System is refers to an electronic communication system by means of wires/cables between various individuals situated at comparatively distant locations within a certain premises. The various location are known as stations. In this project, the intercom is designed in full duplex mode by replacing master-substation. Master-substation system refers to a system that using only one amplifier and installed at the master controller’s location. An audio amplifier and an auto ringing facility (buzzer) are incorporated in this intercom. The Versatile Intercom works without a handset which means the operator merely can speak into intercom from the front. The need of a handset in any such full duplex intercom circuit is obviated by a mic-speaker pair. A detail description of the components used to implement the circuit together with explanation of how the circuit operates is also included. The proposed project will provide a better solution in ‘point-to-point’ communication which means the operator can communicate directly to one and another